We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
99
1
avatar

what is z in -1/3+2z=-5/6

 Apr 10, 2019

Best Answer 

 #1
avatar
+1

\(-\frac{1}{3}+2z=-\frac{5}{6}\\ -\frac{2}{6}+2z=-\frac{5}{6}\\ 2z = -\frac{3}{6}\\ 2z = -\frac{1}{2}\\ z = -\frac{1}{4}\)

.
 Apr 10, 2019
edited by Guest  Apr 10, 2019
 #1
avatar
+1
Best Answer

\(-\frac{1}{3}+2z=-\frac{5}{6}\\ -\frac{2}{6}+2z=-\frac{5}{6}\\ 2z = -\frac{3}{6}\\ 2z = -\frac{1}{2}\\ z = -\frac{1}{4}\)

Guest Apr 10, 2019
edited by Guest  Apr 10, 2019

8 Online Users

avatar